2022
DOI: 10.1177/10760296221086286
|View full text |Cite
|
Sign up to set email alerts
|

Report of Low Incidence of Thrombosis with Early Prophylaxis in Hospitalized Patients with COVID-19 from Two Saudi Tertiary Centers

Abstract: Background Thrombotic events can increase the COVID-19 associated disease mortality. The administration of prophylactic anticoagulants had been shown to decrease the incidence of thrombosis, mortality, and ICU admission rates in COVID-19 patients. Aims The present study investigates the rate of thrombosis with early anticoagulation prophylaxis, the various risk factors for thrombotic events, and the overall survival rate in hospitalized COVID-19 cases. Methods In this prospective observational study, 425 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…In our cohort, hypofibrinolysis was observed in 22 of 446 (4.9%) COVID-19 patients, with more cases of hypofibrinolysis than hyperfibrinolysis. A similar study reported a lower incidence of thrombosis in 1.9% of COVID-19 patients [ 14 ]. However, this finding may be due to the administration of prophylactic anticoagulants earlier in the course of the disease.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In our cohort, hypofibrinolysis was observed in 22 of 446 (4.9%) COVID-19 patients, with more cases of hypofibrinolysis than hyperfibrinolysis. A similar study reported a lower incidence of thrombosis in 1.9% of COVID-19 patients [ 14 ]. However, this finding may be due to the administration of prophylactic anticoagulants earlier in the course of the disease.…”
Section: Discussionmentioning
confidence: 90%
“…Diagnosis of SARS-CoV-2 was confirmed according to the World Health Organization guidelines, nasopharyngeal swabs with reverse transcriptase real-time polymerase chain reaction (RT-PCR) for SARS-CoV-2 were used to confirm the diagnosis of COVID-19 in all patients. According to our hospital’s guidelines for the management of COVID-19 patients, thromboprophylaxis (with unfractionated heparin or low-molecular-weight heparin) was administered to all adult patients and 50% of pediatric patients on the same day of hospital admission or two days later [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Pediatric patients admitted with COVID‐19 are also at an increased risk of VTE 10–12 . In contrast to adult guidelines, pharmacologic prophylaxis is suggested for children admitted with COVID‐19 who either have an elevated D‐dimer levels or have additional risk factors for VTE 12 .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Pediatric patients admitted with COVID-19 are also at an increased risk of VTE. [10][11][12] In contrast to adult guidelines, pharmacologic prophylaxis is suggested for children admitted with COVID-19 who either have an elevated D-dimer levels or have additional risk factors for VTE. 12 In a phase 2 study of pharmacologic prophylaxis with enoxaparin in pediatric patients admitted with COVID-19, no patient experienced clinically significant bleeding.…”
Section: Introductionmentioning
confidence: 99%